Exceeding Expectations: A Historical Analysis of Student Power and Self-Determination - Brewer, David (Disability Studies Quarterly, 2002)
This paper explores theories of student power and self-determination that evolved over the last century, and their relationships to general and special education practices. Historical events, such as the industrial revolution, changes to the workforce, and responses from the educational community are explored through the eyes of educational sociologists and theorists. Lines are drawn, connecting students of lower economic classes, students with disabilities, the School-to-Work Opportunities Act and "self-determination" as described by the 1998 Amendments to the Rehabilitation Act of 1973. To improve student graduation, postsecondary participation and income rates, policy makers and community members must provide both the capacity, instruction and opportunity for all students to learn skills of self-determination, and design their educational programs. Indicators to increase student self-determination are organized into a table for planning. "The difficult thing to explain about how middle class kids get middle class jobs is why others let them. The difficult thing to explain about how working class kids get working class jobs is why they let themselves." Paul E. Willis, Learning to Labour (p.1)